El mercado en el segmento de las parejas sin hijos en Villavicencio (Colombia) (Revista cientifica In Vestigium Ire, 2016)
This article discusses how consists demand and supply of goods and services to meet the needs of couples formed by double income no kids called Dink segment. Also review some studies in Colombia and Mexico, to do qualitative methodology was implemented by interviewing 30 couples of different ages and socioeconomic levels. Similarly informa- tion and response with hotels, restaurants and construction, compared to the emergen- ce of these segments are met. The study was conducted in Villavicencio with the aim of characterizing the behavior of consumption of the Dink couples, so that local companies can identify business opportunities designed to meet the needs and expectations of that segment.
Keywords: Supply; demand; Double income no kids Dink